Breastfeeding in the context of the COVID-19 pandemic: A discussion paper. Issue 1 (February 2022) - Walker, Karen; Green, Janet; Petty, Julia; Whiting, Lisa; Staff, Lynette; Bromley, Patricia; Fowler, Cathrine; Jones, Linda K.
Abstract: Breastfeeding offers one of the most fundamental global health benefits for babies. Breastmilk is lifesaving, providing not only nutrition but immunologic benefits and as such is strongly supported by the World Health Organization and leading healthcare associations worldwide. When the COVID-19 pandemic started in 2020, the impact of the restrictions to prevent the spread of the disease created challenges and questions about provision of safe, quality care, including breastfeeding practices, in a new 'normal' environment. Mothers were temporarily separated from their babies where infection was present or suspected, parents were prevented from being present on neonatal units and vital breastfeeding support was prevented. This discussion paper provides an overview of essential areas of knowledge related to practice for neonatal nurses and midwives who care for breastfeeding mothers and babies, in the context of the COVID-19 pandemic and the latest global guidance. Three areas will be discussed; the protective benefits of breastfeeding, keeping breastfeeding mothers and babies together and supporting mothers to breastfeed their babies. Finally, care recommendations are presented to serve as a summary of key points for application to practice for neonatal nurses and midwives.